VIRTUAL MATHEMATICS KITS (VMK): MEMPROMOSIKAN MEDIA DIGITAL DALAM LITERASI MATEMATIKA - Sholikhah, Octarina Hidayatus; Pradana, Lingga Nico (Profesi Pendidikan Dasar, 2018)
The digital era makes education begin to be contaminated with technology. This study aim to determine the effectiveness of Virtual Mathematics Kits (VMK) viewing by student' mathematical literacy. The VMK was used in extracurricular activities based on mathematical literacy. 83 elementary school students (grade 5) in 4 school participated in this study. There were two intervention classes and two non-intervention classes. All classes were given mathematical literacy activities for 6-weeks period (90-min each week). The VMK used in intervention classes. The activities focus on student' ability to make ideas, reasoning and solve various mathematical problem. The mathematical literacy activities led to improvements in both of two classes. However, the use of VMK make student' mathematical literacy much better. The VMK support student to reason and manipulated mathematical object although students have difficulty to operate VMK. This study showing the use of digital media (VMK) support student' mathematical literacy.